Determinants Of Non-Tax State Revenue In Five Asean Countries: The Mediating Role Of Fiscal Accountability - Sinaga, Murbanto; Hasyim, Sirojuzilam; Syafii , M. (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study analyzes the determinants of non-tax state revenue (NTSR) in five ASEAN countries—Indonesia, Malaysia, Thailand, Vietnam, and the Philippines by incorporating fiscal accountability as a mediating mechanism. Using balanced panel data for the period 2018–2023 and applying multiple linear regression and path analysis, the study examines the effects of economic growth, commodity prices, government effectiveness, digital governance, and trade openness on non-tax revenue performance. The results indicate that government effectiveness is the most significant and robust determinant of NTSR, highlighting the central role of institutional capacity in revenue mobilization. Economic growth does not exert a significant direct effect, while commodity prices are negatively associated with NTSR once fiscal accountability is considered, reflecting vulnerability to external price shocks. Digital governance and trade openness do not directly improve non-tax revenue outcomes; however, fiscal accountability functions as a complementary mechanism that enhances the effectiveness of institutional and structural factors. Overall, the findings emphasize that sustainable non-tax revenue mobilization depends primarily on effective governance and accountability frameworks.